PENGEMBANGAN BOARD GAMES PUNAKAWAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN - Widiyono, Danang Wahyu; Eka Wati, Risma Syafira; Pinasti Putri, Rheyn Wahyu; Ika Mawarni, Tiyas Suci; Ariyanto, Restu Dwi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
This study aims to increase student learning motivation by using the Punakawan board games. The scope is based on the findings of preliminary studies related to student motivation to decline during the COVID-19 pandemic, students show a lazy attitude by not following lessons, rerely appear when Google Meet, always late because they are tight by signal, cannot understand and understand the material. Overall, the value decreases, the enthusiasm for learning drops dramatically, there is a sense of boredom because the learning delivered is monotonous, wasting games and resulting in decereased learning outcomes for some students. So, it is necessary to make innovative media board games to increase student motivation. The method used is Reseach and Development (Borg dan Gall, 1983). This research only reached the fifth stage of testing, namely expert testing. In this article, we come to br conclusion of the result from expert test and 1 user test for Guidance and Counseling teacher test, it shows a score of 81% which is in the percentage range or the categories suitable for use so that the development of the Punakawan board games is suitable to br used to increase student learning motivation.